HABENULA RESPONSES DURING APPETITIVE AND AVERSIVE CONDITIONING IN MAJOR DEPRESSIVE DISORDER. Issue 8 (9th July 2014) - Lawson, Rebecca P; Nord, Camilla L; Seymour, Ben; Thomas, David L; Dolan, Raymond J; Dayan, Peter; Weiskopf, Nikolaus; Roiser, Jonathan P
Abstract : Objective: The lateral habenula (LHb) has been shown to respond to cues that predict aversive stimuli in non-human primates (Matsumoto & Hikosaka, 2009, Nat Neurosci, 12 (1), 77–84) and has been implicated in reinforcement processing and the pathophysiology of major depression (MDD) (Roiser et al, Biol Psychiatry, 66 (5), 441–450), possibly via reciprocal connections with monoaminergic nuclei. We report the first high-resolution fMRI investigation of haemodynamic responses during appetitive and aversive conditioning in the LHb in unipolar MDD. Additionally, we report the first assessment of tonic habenula function using quantitative Arterial Spin Labelling (ASL) in MDD. Method: Unmedicated MDD patients (n=26) and matched controls (n=26) performed a Pavlovian conditioning task where they were exposed to conditioned stimuli (CSs) that preceded reinforcing outcomes (win £1; lose £1; and painful electric shock) in a probabilistic manner. Neural responses were monitored using high-resolution T2* echo-planar imaging (1.5 mm isotropic), and T1-weighted (0.77mm isotropic) images were obtained to accurately identify the habenula (Lawson, et al., 2013, NeuroImage, 64 (0), 722/727). Breathing and heart-rate data were collected to correct for pulse-related artefacts. Using a temporal difference learning algorithm, trial-by-trial values for win, loss and shock predicting CSs were derived for each subject and used as parametric modulators in the fMRI analysis. Additionally, to investigate tonic habenula function, high-resolution ASL images were acquired to quantitatively assess baseline blood flow in the habenula. Results: We replicated our previous result that habenula responses were positive to shock-predicting CSs in healthy volunteers (Lawson et al, submitted). We found no significant group differences in habenula responses to win and loss CSs (Ps>0.7), but surprisingly habenula responses to the value of shock CSs were negative in MDD subjects (P<0.05) and significantly different to controls (p<0005). However, there were no significant group differences in baseline blood flow (P>0.6) or habenula volume (P>0.5), ruling out tonic habenula function or grey matter volume differences as an explanation for our functional results. Conclusion: These surprising results, which cannot be accounted for by group differences in tonic habenula activity or habenula volume, reflect a difference in how depressed patients process aversive stimuli and have important implications for understanding the constructs of anhedonia and learned helplessness.